SINERGISITAS LEMBAGA SWADAYA MASYARAKAT DALAM MENYEJAHTERAKAN MASYARAKAT DI MASA COVID-19: (Studi Pada Yayasan Pemberdayaan Insan Mandiri) - Sriyoto; Siti Ngainnur Rohmah (Jurnal Penelitian Multidisiplin Ilmu, 2022)
Non-governmental organizations have a focus on improving the welfare of the community. One of its branches is the foundation. The presence of the foundation also plays an important role in improving the welfare of the community. The existence of the Covid-19 virus has become an obstacle for people to meet their needs due to restrictions on activities by the government. Therefore, the synergy of the foundation is needed to be one of the ways to overcome these problems. The focus of the research in this thesis is on how the synergy between the law on social welfare and the Yayasan Pemberdayaan Insan Mandiri and the role of the Yayasan Pemberdayaan Insan Mandiri in improving community welfare during Covid-19. The purpose of the research focus is to determine the success of the synergy between the law on social welfare and the role of the Yayasan Pemberdayaan Insan Mandiri in improving community welfare during Covid-19. This study uses qualitative methods with descriptive approach legislation and social. Data collection is done by interview, observation, and documentation techniques. To check the validity of the data using source triangulation and triangulation of data collection. The results of this study indicate that there is a conformity to the synergy between the law on social welfare and also the continuity of the role of the Yayasan Pemberdayaan Insan Mandiri in improving community welfare during Covid-19.